“Peran Teknologi dalam Mewujudkan Good Governance: Perspektif Teori Administrasi Publik” - Elvia, Viny; Adnan, M. Fachri; Khaidir, Afriva (Global Action and Education for Society, 2025)
This research aims to explore the role of technology in creating good governance in the public sector, especially in the digital era which is characterized by the rapid adoption of information and communication technology. The method used in this research is a literature review, which involves analyzing literature related to public administration theory and innovation in public sector organizations. This research identifies various challenges faced, such as gaps in access to technology, public understanding of the use of technology, and bureaucratic readiness to adapt to change. The main issue raised is how technology can be effectively integrated into good governance practices to improve the quality of public services. The research results show that innovation through information technology, such as e-government and big data, has an important role in increasing transparency, accountability and responsiveness of public services. Despite progress in the application of technology, challenges remain, including the need to increase public understanding and skills and the readiness of the bureaucracy to adopt change. The conclusion of this research confirms that to achieve effective good governance, the government needs to encourage innovation in public services by utilizing the latest technology. With these steps, it is hoped that the quality of public services can improve, and the public can be more involved in the decision-making process, thereby creating a more transparent and accountable government.